Palestine and Israel in the Records of President Harry S. Truman - Al Sharafat, Ayman (AMERICANA E-journal of American Studies in Hungary, 2021)
This article analyses the Palestine Question in the documents and communications of President Harry S. Truman and aims to determine the reason behind President Truman’s positions towards Palestine and Israel in his records during his work as the US president. It seeks to answer the questions of how Palestine-Israel related references appeared in the documents of President Truman and what the reasons were behind his position. The study applies the ‘realist’ approach to the history of foreign policy and reconciles a variety of historiographies and archives. American presidential communication archives are used in order to collect materials regarding President Truman and his associations with Palestine and Israel. The study finds that Truman was brilliantly able to claim justification on humanitarian principles for having helped the Jewish people in his communications during his presidency, and as a result, sought to gain many political advantages for himself and for his party.